The early-stage evolution of the Neo-Tethys ocean: Evidence from granitoids in the middle Gangdese batholith, southern Tibet. (March 2016) - Meng, Yuanku; Dong, Hanwen; Cong, Yuan; Xu, Zhiqin; Cao, Hui
Highlights: Granitoid rocks crystallized at 169–191 Ma. Zircon data indicate crustal growth in southern Tibet during early Jurassic. Neo-Tethys subduction and active continental margin setting in southern Tibet. Mantle-derived magmas played a significant role in their origin. Abstract: The Gangdese magmatic belt, located along the southern margin of the Lhasa terrane, plays a critical role in understanding the tectonic framework associated with the Indian-Eurasian collision and the crustal growth of the southern Tibet. In this paper, we present a series of results from new petrological, geochemical and geochronological investigations of the granitoid rocks. The granitoids mainly have sub-alkaline compositions and show medium K calc-alkaline affinities, as well as I-type granitoid characteristics. Significant depletions of Nb and Ta, combined with other geochemical features including enrichments of LILEs and LREEs confirm that the parental magmas of these rocks were generated in a subduction-related active continental margin (continental arc environment). Lu-Hf isotopic compositions and relatively low MgO contents indicate that the granitoids might be generated from partial melting of juvenile crust and basaltic lower crust, which is caused by the underplating of mantle materials, and the mantle materials that have been involved in this process. The 191.2–169.2 Ma zircon U-Pb ages of the granitoids reveal middle-early Jurassic magmatic events. Combined with published data in the Gangdese magmatic belt, our study suggests that the northward subduction of the Neo-Tethys oceanic crust beneath the southern margin of the Lhasa terrane probably started no later than 191.2 Ma. Zircons from the granitoids suite display positive ɛ Hf ( t ) values between 10.1 and 15.4 (mean value is 12.7), which correspond to the two-stage model ages ( t DM2 ) in the range of 198–415 Ma, attesting to crustal growth in the southern Lhasa terrane associated with the subduction of the Neo-Tethys oceanic crust. Our study is a systematic report of the granitoid suite in the Gangdese magmatic belt and strengthens the concept that the Neo-Tethys oceanic crust might have experienced a long evolution history.